Incisol, an alcohol with a novel sesquiterpene skeleton from Xenophyllum incisum - de Marchese, María J.A. (2007)
Aerial parts of Xenophyllum incisum (Phil.) V. A. Funk (syn. Werneria incisa Phil.) were collected at 4300 m above sea level in the Departamento Susques, between Susques and Paso de Jama, 30 km before arriving in Paso de Jama. A voucher specimen (LIL 606089) is deposited in the herbarium of the Instituto Miguel Lillo, Tucuman. Aerial parts of this species of the highlands of Northwestern Argentina, Northern Chile and Bolivia, known under the common names pupusa de agua, poposa, are used locally to prepare infusions for the treatment of hepatic disorders, apunamiento (altitude sickness) and chills and for washing rheumatic feet. This species is frequently confused with Xenophyllum poposum (Phil.) V. A. Funk (syn. Werneria poposa Phil.). In folk medicine the uses for both species are essentially the same (Giberti, 1983; Shemluck, 1982).